Self-assembly of bispentadecylphenol substituted perylenediimide with PS-b-P4VP for structure-property insight into the core of core-shell micelles - Roy, Moumita; Rajamohanan, Pattuparambil R.; Ravindranathan, Sapna; Asha, S. K. (ACS Applied Polymer Materials, 2020)
We report the use of a ditopic molecular probe bispentadecylphenol substituted perylenediimide (PBI-PDP) to examine the molecular level self-assembly of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) in tetrahydrofuran (THF). A series of complexes were prepared between PS-b-P4VP copolymers with varying lengths of the 4-vinylpyridine chain and PBI-PDP. Light scattering and NMR spectroscopic studies reveal that the self-assembled structures of the solid complexes are not fully disrupted when the complexes are dissolved in THF. NMR experimental parameters measured for the small probe molecule provide detailed insights into the structure of the assemblies in solution as well as the interaction between the small molecule and the block copolymer. Such insights can have important implications in manipulating the nanostructure of block copolymer micelles to suit various application requirements. The dynamics and distribution of the PBI-PDP molecules within the assemblies in solution show a dependence on the length of the P4VP block. Transmission electron microscopy was employed to study the evolution of morphologies in films prepared from the self-assembled structures in THF solutions.
Keywords: core corona interface; ditopic molecular probe; environment; micelles; perylenediimide; PS-b-P4VP; Self-assembly